What Is a Class? On the Simmelian Art of Learning and Teaching - Vernik, Esteban (Simmel Studies, 2019)
This paper focus on School Pedagogy, a course teached by Simmel at the end of his life in Strasbourg University. The intention is to convey that Simmel’s pedagogy is not an isolated chapter within his theory, but it shows principles present throughout his work and that are here applied in the pedagogical field. For this end, it first briefly outlines Simmel’s trajectory previous to teaching this course; then it concentrates in analyzing key points of the relation between Simmel’s art of teaching and learning and his works as a whole, to conclude which a group of practical points.